2000
DOI: 10.1097/00003246-200006000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of ventilator-associated pneumonia and success in nutrient delivery with gastric versus small intestinal feeding: A randomized clinical trial

Abstract: There is no clear difference in the incidence of VAP in SI compared with G enteral nutrition. Patients given feeding into the SI do receive higher calorie and protein intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(110 citation statements)
references
References 31 publications
4
104
2
Order By: Relevance
“…The risk of aspiration is unaltered by the size of the feeding tube [106], and inconsistently affected by pro-motility agents and different feeding regimes [107,108]. Post-pyloric placement of feeding tubes decreases neither the risk of aspiration nor of ICU-AP [101,109]. There is not enough data to conclude that timing of feeding, position of feeding tubes, type of tube or type of feeding formula can be used as preventive measure for ICU-AP.…”
Section: Route Of Ett (Ie Nasal or Oral)mentioning
confidence: 99%
“…The risk of aspiration is unaltered by the size of the feeding tube [106], and inconsistently affected by pro-motility agents and different feeding regimes [107,108]. Post-pyloric placement of feeding tubes decreases neither the risk of aspiration nor of ICU-AP [101,109]. There is not enough data to conclude that timing of feeding, position of feeding tubes, type of tube or type of feeding formula can be used as preventive measure for ICU-AP.…”
Section: Route Of Ett (Ie Nasal or Oral)mentioning
confidence: 99%
“…10 Notwithstanding our disappointing clinical experiences with the technique of nasoduodenal enteral feeding, including in critically ill ICU patients, 10 there has subsequently been considerable interest in the technique of postpyloric enteral feeding in the ICU patient, particularly in respect of reducing the incidence of aspiration pneumonia. [13][14][15][16][17][18][19][20][21][22] In attempting to assess and compare the results of the 10 controlled studies, [13][14][15][16][17][18][19][20][21][22] one is forced to conclude that the term postpyloric almost certainly refers to nasoduodenal tube placement and that some authors may have been somewhat optimistic in thinking that they had achieved intrajejunal tube placement. Overall, the results of the studies have been conflicting, and no clear consensus on the efficacy of postpyloric feeding in reducing the incidence of aspiration pneumonia has been documented.…”
Section: 9mentioning
confidence: 99%
“…8,9,23,24 One possible reason for this is that there is a need to aspirate gastric contents during postpyloric feeding. It is unlikely that this was performed in the above studies, [13][14][15][16][17][18][19][20][21][22] as the available feeding tubes did not incorporate a gastric aspiration port.…”
Section: 9mentioning
confidence: 99%
“…In some studies, there were not significant differences in VAP and mortality rates between patients with gastric or postpyloric feeding [138][139][140][141][142][143][144]. In the meta-analysis by MARIK and ZALOGA [145], which enrolled 522 patients from nine studies, analysis of the 422 patients from seven studies that reported the VAP rate [138][139][140][141][142][143][144] found that gastric feeding showed a trend to higher incidences of VAP (odds ratio 1.44, 95% CI 0.84-2.46) and mortality (odds ratio 1.08, 95% CI 0.69-1.68) than post-pyloric feeding; however, the differences were not statistically significant.…”
Section: Semirecumbent Position (30-45u)mentioning
confidence: 99%